Tolerance of Bone Marrow Cells to Osmotic Stress Effect - Ostankova, L. V.; Kholodnyy, V. S. (Problems of Cryobiology and Cryomedicine, 2002)
The authors have studied the effect of osmotic stress in the solutions of sodium chloride of various concentrations on the integrity, quantitative and qualitative composition, adhesive ability and phagocyte activity of cells of mouse bone marrow (BM). There were defined the limits of changes in osmolarity and cell volume, which do not result in considerable reduction in their integrity and functional activity.